2019
DOI: 10.1002/asia.201900055
|View full text |Cite
|
Sign up to set email alerts
|

Squaraine Dyes: Interaction with Bovine Serum Albumin to Investigate Supramolecular Adducts with Aggregation‐Induced Emission (AIE) Properties

Abstract: Bovine serum albumin (BSA)–squaraine supramolecular adducts with aggregation‐induced emission (AIE) properties were prepared and characterized by spectroscopic methods. While squaraine dyes showed a very low fluorescence quantum yield in water, a great enhancement in the fluorescence of the aggregated BSA adducts was achieved due to the abnormal aggregation‐induced emission properties of squaraines. The adducts formation was studied from a kinetic point of view showing unexpected structure–properties relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
(67 reference statements)
4
22
0
Order By: Relevance
“…However, as most of fluorescent probes, in physiological conditions, squaraine dyes tend to form aggregates that lead to fluorescence quenching therefore limiting their wide applications. As reported in previous studies, squaraine dyes exhibit a fluorescence turn-on when bound to proteins which translate in an increase in fluorescence intensity, quantum yield and lifetime due to the changes in the surrounding environment [27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 59%
“…However, as most of fluorescent probes, in physiological conditions, squaraine dyes tend to form aggregates that lead to fluorescence quenching therefore limiting their wide applications. As reported in previous studies, squaraine dyes exhibit a fluorescence turn-on when bound to proteins which translate in an increase in fluorescence intensity, quantum yield and lifetime due to the changes in the surrounding environment [27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 59%
“…Experimentally, these challenges can be overcome through the 'chaperoning' of fluorescent probes with proteins such as albumin. [22][23][24][25] NIR fluorescent indolizine cyanine and indolizine squaraine dyes (SO 3 C5 and SO 3 SQ, Figure 1) were previously equipped with water solubilizing sulfonate groups to study their photophysical properties in a biologically relevant medium. [21] Higher quantum yields were discovered while studying the dyes in fetal bovine serum (FBS) compared to water with SO 3 SQ, reaching a quantum yield of 58.3 % in FBS compared to 0.3 % in water.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation often leads to quenched emissions and poor quantum yields with these classes of materials, limiting their practical use in many applications. Experimentally, these challenges can be overcome through the ′chaperoning′ of fluorescent probes with proteins such as albumin [22–25] . NIR fluorescent indolizine cyanine and indolizine squaraine dyes (SO 3 C5 and SO 3 SQ, Figure 1) were previously equipped with water solubilizing sulfonate groups to study their photophysical properties in a biologically relevant medium [21] .…”
Section: Introductionmentioning
confidence: 99%
“…16 A considerable number of research studies have also been carried out to develop new scaffolds and AIE cores and in this direction, Tanaka et al, Liu et al and Voskuhl et al have reported the design of various AIEgens based on bis(o-carborane)-substituted benzobithiophene structures, 17 phenanthro[9,10-d]imidazole 18 and alkylated aromatic thioethers, 19 respectively. Barolo et al and Ramstro ¨m et al have also studied the AIE effect and observed it in squaraine dyes 20 and N-amidinated fluoroquinolones, 21 respectively. AIE dyes are non-fluorescent in completely soluble or monomer state but reveal fluorescence emission as the aggregates are formed.…”
Section: Introductionmentioning
confidence: 99%